Old aviances ; Iodine deficiency ; Spyro-Gyra [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Rejection of the twelve senate committee on the American military bases and the relation between the Philippines and the United States; Goiter problem on the women of Cordillera due to lack of iodine; A jazz group named Spyro Gyra whose music were purely jazz.
Old aviances (19 min.) -- Iodine deficiency (15 min.) -- Spyro-Gyra (16 min.)
VHS.
Keywords: Goiter -- Philippines -- Cordillera; Jazz musicians -- United States; Military bases, American -- Philippines; Spyro Gyra; Philippines -- Foreign relations -- United States; United States -- Foreign relations -- Philippines